DEVELOPMENT OF STANDARD OPERATING PROCEDURES FOR SPANNING PATIENTS WITH FRACTURES IN THE EMERGENCY ED OF BALIMED HOSPITAL, DENPASAR - Made Oktaviani Bulan Trisna; Ni Made Dewi Wahyunadi Buntari Agustini; Ni Luh Putu Inca Buntari Agustini; Ni Putu Yustina; I Wayan Edi Sanjana; I Gede Rendy Arizona Vallentino; Pige Rade Sairo (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Background: Emergency services provided to fracture patients include splinting, which is a nursing action to relax or rest (immobilize) the injured body part using a splint with the aim of reducing pain and preventing excessive bone displacement. Splinting is a technique used to immobilize or stabilize a broken limb. Immobilization can reduce pain, swelling, muscle spasms , epistaxis, and the risk of fat embolism Purpose: The aim of this study is to analyze the development of standard operating procedures for splinting in patients with fractures in the emergency room of Balimed Hospital, Denpasar. Methods: The method used was a case report with the ADDIE approach, which is an abbreviation of the stages, namely Analysis, Design, Development, Implementation, and Evaluation. Its use is for various forms of product development such as models, strategies, methods, or media. Results: The same thing as HIPPII, (2019) which informs that the steps and principles of writing an SOP are by implementing a policy review that underlies a procedure or work process, considering the procedure, when the SOP was created, searching for literature and other related information that supports the procedure, seeking input from staff and officers, writing down the equipment or facilities needed, determining who is authorized to carry out the procedure, writing down indications or contraindications and underlining risks, warnings, and other things that are needed. Conclusion: The effectiveness of the SOP that has been developed on patients and evaluating patient comfort and controlling pain due to fractures experienced.